COPING BEHAVIOR OF BENJAMIN BUTTON IN ERIC ROTH'S THE CURIOUS CASE OF BENJAMIN BUTTON MOVIE (2008): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PURWANTORO, IMAN HARSE (2010)
The major problem of this study is to reveal the coping behavior of Benjamin Button reflected in The Curious Case of Benjamin Button movie. The objectives of the study are; to analyze the structural elements of the movie and to analyze the character of Benjamin Button based on individual psychological analysis. This study belongs to qualitative study. In this method, there are two types of data sources, which are used, namely primary data and secondary data sources. The primary data source is the movie The Curious Case of Benjamin Button, meanwhile the secondary data source are the other sources related to the analysis such as internet, books and other references which are related to this study. In analyzing the data, he applies two approaches. Firstly, structural approach is used to analyze the element of the movie. It contains of characterization, setting, point of view, plot, theme, and casting. Secondly, the individual psychological approach is use to analyze the coping behavior of Benjamin Button to reach his goal of life. The result of the research shows that the character of Benjamin Button has some problem dealing with the abnormal physical growth and psychological development in the story, but he tries to solve his problem. He has believed that nothing is impossible to be true and he has proved it.